#### Answer

$(r+3)(3r-5)$

#### Work Step by Step

The factor $(r+3)$ is common to both terms.
Factor out $r+3$ to obtain:
$=(r+3)[(5r-6)-(2r-1)]
\\=(r+3)[5r-6-2r-(-1)]
\\=(r+3)(5r-6-2r+1)
\\=(r+3)(3r-5)$

Published by
Pearson

ISBN 10:
013421742X

ISBN 13:
978-0-13421-742-0

$(r+3)(3r-5)$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.